Analysis of The Specific Features of Legislative Initiative - Boymurodov Botir Panji ugli (International Journal of Law And Criminology, 2025)
This article delves deeply into the procedural aspects of exercising the right of legislative initiative. The right of legislative initiative plays a crucial role in democratic societies, as it allows citizens, organizations, and state bodies to participate in the development and adoption of draft laws. The article analyzes the stages, requirements, and limitations of exercising the right of legislative initiative. Furthermore, the article compares the experience of implementing the right of legislative initiative in various countries and develops proposals for improving the right of legislative initiative in the Republic of Uzbekistan.